Evaluasi Displacement Horizontal Pasar Raya Padang Blok IV Berdasarkan Gaya Gempa Pada SNI-03-1732-2019 - majid maulana; Eka Juliafad (Universitas Negeri Padang, 2022)
Pasar Raya Padang Market blok IV was built in 2016 as an resisting earthquake building based on SNI-1726-2012. The building has a building dilatation with a distance of 1 cm. The purpose of this study was to evaluate the dilatation distance of the Raya Padang Blok IV market building based on the seismic forces required in SNI-1726-2019.The evaluation method used in this research is numerical analysis method by using non-linier pushover over analysis. The numerical model used 3D model with the input material and the earthquake loading according to the proposed design and the response spctrum from SNI-1726-2019. This research evaluate overall structural performance of the buildings based on ATC-40. The results of the pushover analysis of the Raya Padang Blok IV Market building are the maximum displacement of the building of 9.936 mm, the allowable displacement is 320 mm, and the shear force to occur is 1409.094 KN, while the design shear force is 1508.3265. The results of this analysis conclude that the existing dilatation distance in the existing building meet the minimum requirement need based on this study. Building performance level reachs Immidiate Occupancy Level which means the building can be functioned immideately as the eartquake ends.